Analisis Propagasi Gelombang Radio Menggunakan DLink 624 pada Jurusan Teknik Elektro Universitas Syiah Kuala - . Syahrial; Hubbul Walidaini; . Mulyadi (Jurnal Rekayasa Elektrika, 2012)
Telecommunication technology nowadays tries to implement Personal Communication System (PCS) which has Personal Mobility (PM) and Terminal Mobility (TM). PCS can be define as radio technology that uses Radio Frequency (RF) as a transmission medium, which is small and light, and can be implemented indoor and outdoor. One equipment that implements this technology is called D-Link. The application of D-Link is to communicate among users either indoor or outdoor. Research methodology includes deciding the parameters and calculating the path loss between base station and portable station at the second floor of Electrical Engineering Department Syiah Kuala University. The final result was that the communication between the base station and portable station in the rooms at the second floor could exist but the process is rather slow and can experience discontinuity. Those were happenbecause the receiver’s power was below the threshold of the portable station level, i.e.. -40 dB.